Hydroboration kinetics: Unusual kinetics for the reaction of 9-borabicyclo[3.3.1]nonane with representative alkenes - Brown, Herbert C. (1980)
The kinetics of hydroboration of alkenes with 9-borabicyclo[3.3.1]nonane dimer, (9-BBN)(2), exhibit interesting characteristics. With more reactive alkenes, such as 1-hexene, 2-methyl-1-pentene, 3,3-dimethyl-1-butene, and cyclopentene, the reaction exhibits first-order kinetics, first order in (9-BBN)(2) and zero order in alkene. On the other hand, with less reactive alkenes, such as cyclohexene, 1-methylcyclohexene, and 2,3-dimethyl-2-butene, the reaction exhibits three-halves-order kinetics, first order in alkene and one-half order in (9-BBN)(2). These kinetics can be accounted for in terms of the following mechanism: (9-BBN)(2) ⇄ 2 9-BBN 9-BBN + alkene → B-alkyl-9-BBN In the case of the more reactive alkenes, the rate-determining step is the dissociation of the dimer. With less reactive alkenes, the reaction of the alkene with the monomer becomes the rate-determining step. For certain alkenes, such as 2-methyl-2-butene and cis-3-hexene, neither of the two steps is a decisive rate-determining step. Therefore, the reaction exhibits kinetic behavior between that of first- and three-halves-order kinetics.